School-based nutrition interventions had impacts on dietary diversity and meal frequency of adolescent girls in Ethiopia - Sununtnasuk, Celeste; Berhane, Hanna; Kim, Sunny S.; Menon, Purnima; Oumer, Abdulaziz; Sanghvi, Tina; Walissa, Tamirat (Elsevier, 2022)
Adolescence is a critical period of physical and psychological development, especially for girls as poor nutrition can affect their well-being as well as the well-being of their children. In Ethiopia, where the population is very young, evidence on the nutrition of adolescent girls and their determinants is scant. We tested the impact of a package of nutrition interventions delivered primarily through schools and implemented by Alive & Thrive (A&T) on the diet of adolescent girls.